Rare cases in two Chinese MEN2A families with RET C634Y germline mutation—a homozygous female patient and heterozygous identical twins: a systematic review of literature - Qi, Xiao-Ping; Weng, Yu-Ting; Chen, Zhen-Yu; Zhang, Mei-Xian; Yang, Xiao-Ling; Cao, Zhi-Lie; Zhang, Xue-Xing; Zhu, Wen-Bo; Yu, Hong-Yuan; Chen, Wei-Ying; Chen, Ji-Ya; Li, Fei-Ping (Frontiers in Endocrinology, 2026)
BackgroundGermline RET-p.C634Y heterozygous mutations are predominant in MEN2A, but homozygous cases and MEN2A-affected identical twins remain poorly characterized.SummaryWe report two MEN2A families—a homozygous female patient and heterozygous male twins, all with RET-p.C634Y mutations and classic MEN2A manifestations. A systematic review identified 18 homozygous cases from 10 families, involving exons 11, 14, and 15, containing nine types of mutations, presenting a female (55.6%) and moderate-risk mutation (61.1%) predominance. Overall, 83.3% of the 18 patients with homozygous mutations and 30.6% of the 49 patients with heterozygous mutations from the same generation had medullary thyroid carcinoma (MTC). The homozygous mutations had a higher penetrance rate of MTC (P < 0.001) and rates of node-positive metastasis (8/15 vs. 1/15, P = 0.017). However, the comparison of the mean age at initial MTC diagnosis between patients with homozygous and heterozygous mutations [33.40 ± 17.97 (5–59) vs. 39.60 ± 12.94 (14–61) years], as well as in moderate-risk and high-risk patients with homozygous mutations [36.89 ± 16.21 (13–59) vs. 28.17 ± 20.72 (5–56) years], showed no significant differences (all P > 0.05). Additionally, the mean age at diagnosis and the incidence of pheochromocytoma did not differ significantly [(37.75 ± 18.43) vs. (39.5 ± 3.54); 27.8% vs. 13.3%; all P > 0.05]. Clustered data for identical twins diagnosed with MEN2 were also analyzed, including one with MEN2A and two with MEN2B. All three pairs of identical twins exhibited varying clinical presentations, expressivity of MEN2-related MTC and/or pheochromocytoma, and associated biomarker levels.ConclusionsHomozygous MEN2A accelerates MTC onset and increases metastasis risk, but there is no evidence of association with the development of pheochromocytoma. Consanguineous marriage could increase homozygosity in offspring and the number of affected individuals. Expressivity and clinical progression can vary even with the same genetic backgrounds, and identical twins should also be subject to individual management.